Characteristics of 24 SARS-CoV-2-Sequenced Reinfection Cases in a Tertiary Hospital in Spain - Borras-Bermejo, Blanca; Piñana, Maria; Andrés, Cristina; Zules, Ricardo; González-Sánchez, Alejandra; Esperalba, Juliana; Parés-Badell, Oleguer; García-Cehic, Damir; Rando, Ariadna; Campos, Carolina; Codina, Maria Gema; Martín, Maria Carmen; et al. (Frontiers in Microbiology, 2022)
Background: Since the emergence of SARS-CoV-2, a main concern is whether reinfections are possible, and which are the associated risk factors. The aim of this study was to describe clinical and molecular characteristics of 24 sequence-confirmed reinfection SARS-CoV-2 cases along one year in Barcelona (Catalonia, Spain). Methods: Patients with >45 days between two positive PCR test regardless of symptoms and negative test between episodes were initially considered as suspected reinfection cases during weeks 11/2020-05/2021. Whole-genome sequencing was performed to confirm genetic differences between consensus sequences and for phylogenetic studies based on PANGOLIN nomenclature. Reinfections were confirmed by number of mutations, change in linage or epidemiological criteria. Results: From 39 reported suspected reinfection cases, complete viral genomes could be sequenced from both episodes of 24 patients, all confirmed as true reinfections. With a median age of 44 years (IQR 32-65), 66% were females and 58% were health care workers. Median days between episodes were 122 (IQR 72-199), occurring one third within 3 months. Reinfection episodes were frequently asymptomatic and less severe than primary infections. The absence of seroconversion was associated with symptomatic reinfections. Only one case was reinfected with a variant of concern. Conclusions: SARS-CoV-2 reinfections can occur in shorter time than previously reported and mainly found in immunocompetent patients. Surveillance through whole-genome sequencing is useful to identify viral mutations associated with immune evasion.